The anterior cruciate ligament inury prevention program: a meta-analysis - Yang, C. S.; Lee, G. S.; Kim, J. G.; Lee, Y. S.; Chung, C. S.; Shin, I. S.; Kwon, Y. H.; Lee, S. I.; Yoo, J.; Lim, B. O. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to evaluate the effect of a neuromuscular protocol on the prevention of anterior cruciate ligament (ACL) injury by performing meta-analysis. An extensive literature review was conducted to identify relevant studies, and eventually, only seven randomized controlled trials or prospective cohort studies were included in the analysis. Subgroup analysis revealed that an age under 18, soccer rather than handball, pre- and in-season training rather than either pre or in-season training, and the plyometrics and strengthening components rather than balancing were significant. Metaanalysis showed that pre- and in-season neuromuscular training with an emphasis on plyometrics and strengthening exercises was effective at preventing ACL injury in female athletes, especially in those under 18 years of age.